FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP PETANI TERHADAP PROGRAM UPSUS PAJALE DI DISTRIK SUKOHARJO - Pradite Nimas Ayu A; Suminah Suminah; Arip Wijianto (Universitas Sebelas Maret, 2018)
This study aims to study farmer attitude in UPSUS PAJALE program in Sukoharjo regency, to examine the factors that influence farmers attitudes in UPSUS PAJALE program in Sukoharjo regency, to examine the influence of factors influencing farmer attitude on UPSUS PAJALE program in Sukoharjo regency. The basic method of research is quantitative by survey technique. The location of the research is determined purposively in Sukoharjo District, precisely in the outboard village and Sraten (Gatak), Duwet and Menuran (Baki), and Klumprit and Sapen (Mojolaban) villages with the consideration of production in 2015 showing the highest production (Gatak) medium (Tray), and low production (Mojolaban). The sampling method used is proportional random sampling, with a sample size of 80 farmers. The data obtained through interviews, observation, and documentation. Data analysis using multiple linear regression. The result of research shows that the factors that influence attitude are non-formal education category is very high at 76.25%, the influence of other people who are considered high category importance is 57,50%, high category mass media equal to 52,50%, very category experience high of 78.75%, and the economic environment with katogori of 87.50%. There is a significant influence between non- formal education, the influence of others who are considered important, experience, mass media at the level of 95% confidence and there is no significant influence between the economic environment on farmers attitude on UPSUS PAJALE program.